DESIGN AND EXPERIMENTAL STUDY ON KEY COMPONENTS OF WOOD PILE CRUSHER - SHUI JiaKun; LIAO Kai; YANG DaoYu; LI LiJun; GAO ZiCheng; SONG LiNa (Jixie qiangdu)
The A pile pulverizer was designed to solve the problem that pine wood pile was difficult to deal with.The abandoned spiral hob was used to treat the infected wooden pile, and the parameter-hobbing performance of the tool was studied. Firstly, The mechanical model of tool hobbing is established to analyze the relationship between pile and tool; Secondly, BBD method was used to set the three-factor three-level experiment scheme with feed, rotation and ABAQUS software is used to perform hobbing force simulation calculation, numerical fitting is carried out between the calculation results and the inluencing factors, and the interaction relation of each factor is analyzed to obtain the hobbing force prediction function model; Thirdly, according to the function and the simulation experiment, the optimum parameters are the minimum hobbing force when the feed speed is 60 mm/s, the rotation speed is 1 000 r/min and the hobbing depth is 15 mm. Finally, The results show that the correction coefficient of the function model is 92.4%, indicating that the function fitting degree is good and can accurately reflect the changing law of the hobbing force; Combined with experimental verification, the deviation between compute and experimental results is 14%～16.4%,indicating that the mathematic model has a good engineering reference value for actual hobbing.